2001
DOI: 10.1080/003655201750305495
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids Impair Intestinal Epithelial Wound Repair Mechanisms In Vitro

Abstract: Prednisolone and budesonide inhibit intestinal epithelial cell restitution and proliferation in vitro. Both processes play a key role in the rapid resealing of the mucosal barrier following intestinal injury. Thus, impaired intestinal epithelial wound healing under corticosteroid therapy in vivo may be caused by inhibition of intestinal epithelial cell restitution and proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 34 publications
2
20
1
1
Order By: Relevance
“…In the present study, a dose-dependent inhibition of intestinal epithelial restitution by Dex was observed, consistent with results described for budesonide and prednisolone [18], [19]. Strikingly, neither CpdA nor ZK216348 showed negative effects on intestinal epithelial migration or proliferation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, a dose-dependent inhibition of intestinal epithelial restitution by Dex was observed, consistent with results described for budesonide and prednisolone [18], [19]. Strikingly, neither CpdA nor ZK216348 showed negative effects on intestinal epithelial migration or proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…GCs have been shown to impair intestinal wound healing, thus preventing the full restoration of normal host homeostasis [18], [19], [20]. Usually, after superficial injury, the first step in mucosal healing involves the migration of epithelial cells across the mucosal defect to the wound area, a process termed restitution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct effect of S. stercoralis on the small bowel mucosa can be related to the secreted ecdysteroids as discussed by Genta (42) and identified in other parasitic helminths (43). This hormone is structurally similar to some metabolites of human steroids (44) from which corticosteroids are known to induce apoptosis concomitant with inhibition of cell proliferation (45,46).…”
Section: Discussionmentioning
confidence: 97%